ANALISIS HASIL BELAJAR DILHAT DARI JENIS KELAMIN MAHASISWA PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN UNIVERSITAS RIAU PADA MASA PANDEMI COVID 19 - Infa Febrisal Saputra; Gimin Gimin; Sri Erlinda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract :The background of this analysis is due to online learning which causes the need for research to see learning outcomes seen from the gender. The problems of this analysis is how learning results perspectives by counting the gender of the students of Pancasila and Civic Education in University of Riau during the pandemic covid-19. This analysis is using type of quantitative and descriptive quantitative research that used the data collection techniques of observation, interviews, questionnaire and documentation. The location of this research are conducted at the Faculty of Teaching and Education of University of Riau. Population to be used in research is PPKn Students.Sample of 66 students of Pancasila and Civic Education consisting of 16 male students and 50 female students in this study.Based on the results of the research acquired, to be specific the aftereffects of the investigation above, it tends to be seen that taking in results are seen from the entire, 75% of men answered